2003
DOI: 10.1021/la035001u
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Solar Cell Using a TiO2 Nanocrystalline Film Electrode Modified by an Aluminum Phthalocyanine and Myristic Acid Coadsorption Layer

Abstract: A dye-sensitized solar cell using a nanocrystalline TiO2 film electrode modified by aluminum phthalocyanine, aluminum 2,9,16,23-tetraphenoxy-29H,31H-phthalocyanine hydroxide (AlTPPc), and a myristic acid adsorbed layer was developed. The UV-vis absorption spectrum of the TiO2 film electrode modified by an AlTPPc and myristic acid adsorbed layer shows that the aggregation of AlTPPc molecules was suppressed by myristic acid. For a cell using AlTPPc adsorbed on a nanocrystalline TiO 2 film electrode, ISC, VOC, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…It has been well established that the coadsorption of DCA leads to an increase in η to a certain extent. 6b,7, 9 We also coadsorbed DCA onto Type-II-dye adsorbed TiO 2 films. As summarized in Table 3, V oc and J sc , and FF somewhat increased upon coadsorption of DCA except Cat-and Dop-sensitized DSSCs.…”
Section: Scheme 3: Proposed Mechanism Partially Responsible For the Imentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that the coadsorption of DCA leads to an increase in η to a certain extent. 6b,7, 9 We also coadsorbed DCA onto Type-II-dye adsorbed TiO 2 films. As summarized in Table 3, V oc and J sc , and FF somewhat increased upon coadsorption of DCA except Cat-and Dop-sensitized DSSCs.…”
Section: Scheme 3: Proposed Mechanism Partially Responsible For the Imentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] A great number of dyes have been tested as sensitizers during the past 15 years in pursuit of high efficiency (η). Accordingly, the η has reached ∼11% in the laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalocyanines [1] are an active focus of intense research for the development of efficient light-to-energy conversion devices. [2][3][4][5][6][7][8][9][10][11][12][13] Such molecules have unique properties in terms of light absorption in the far visible region of the solar spectrum (l = 690 nm) with molecular extinction coefficients (e) higher than 100 000 dm 3 m À1 cm À1 and good chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pH of the aqueous solution hardly affected the adsorption, whereas heat treatment (e.g., of TiO 2 Ͼ 500°C) noticeably lowered the adsorption. [12] In contrast, the synthesis of organic-inorganic hybrids from modified precursors by sol-gel processing usually led to amorphous as-prepared materials and required acidic conditions to favour the ligand exchange for reorganization to generate the crystallization of the inorganic part. Sanchez et al reported a one-step sol-gel method to obtain surface-protected nanocrystalline zirconium, titanium and tin dioxide particles in the presence of acetylacetone and para-toluenesulfonic acid.…”
Section: Introductionmentioning
confidence: 99%